2007
DOI: 10.1002/bp070087t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Synchronization on CD40 Expression and Antibody Production in Hybridoma Cells Stimulated with Anti-mIgG

Abstract: In previous experiments with the 55-6 hybridoma cell line, we showed that cell stimulation with anti-mouse surface immunoglobulin G antibody (anti-mIgG) increased both CD40 expression and specific monoclonal antibody (mAb) production rate. Cell preincubation with lipopolysaccharide (LPS) prior to anti-mIgG stimulation enhanced these results. Moreover, the expression of both CD40 and surface immunoglobulin G (sIgG) were higher for cells in the G1 phase of the cell cycle. Therefore, to determine the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…5a), in a similar way to that observed in a previous work for thymidine synchronization (Martín-López et al 2007a). Both the expression of CD40 and specific productivity declined abruptly after achieving the maximum value, probably provoked both by the loss of synchronization and by the decrease in the concentration of anti-mIgG in the culture medium since, as previously shown, the free anti-mIgG initially added to the culture medium was bound to IgG2a as this was secreted by cells.…”
Section: Cell Cyclesupporting
confidence: 88%
See 3 more Smart Citations
“…5a), in a similar way to that observed in a previous work for thymidine synchronization (Martín-López et al 2007a). Both the expression of CD40 and specific productivity declined abruptly after achieving the maximum value, probably provoked both by the loss of synchronization and by the decrease in the concentration of anti-mIgG in the culture medium since, as previously shown, the free anti-mIgG initially added to the culture medium was bound to IgG2a as this was secreted by cells.…”
Section: Cell Cyclesupporting
confidence: 88%
“…The results showed that some of the factors (HU synchronization, anti-mIgG treatment, a second dose of thymidine, a second dose of HU and LPS treatment) affected stronger CD40 expression (p value \ 0.05), and the increase or decrease in CD40 expression led to increased or decreased mAB productivity; but others factors (preLPS treatment and thymidine synchronization) affected stronger mAB productivity (p value \ 0.05), probably involving metabolic routes different from those of CD40. This shows a complex relationship between mAb productivity and CD40 expression that can not be represented by a simple linear regression as proposed previously (Martín-López et al 2007a). …”
Section: Cell Cyclementioning
confidence: 67%
See 2 more Smart Citations
“…A relationship between cell cycle position, CD40 expression and mAb productivity has also been observed (Martín-López et al 2007c, 2010.…”
Section: Introductionmentioning
confidence: 78%